Child participation as a social strategy for community transformation in the Municipality of Soacha - Marcela Gómez, Nubia; Castro Nemocón, Alba M.; Luz Acero, Mary; Prieto Galindo, William A. (Journal of business and entrepreneurial studie, 2020)
Girls and boys are free subjects to decide on their development and contribute to their environment; to understand their realities is to recognize their possibilities of participation. The objective of this article is to present the spaces generated from Aula Móvil, a project carried out with rural communities in the municipality of Soacha, for the co-construction of an educational proposal that is aware of the levels of child participation. The mixed research method was applied, with interviews, surveys and observation guides to analyze data on their participation from the feeling of caregivers, teachers in training, girls and boys. With the affected results it is corroborated that the participation of children does not have a relevant meaning for the community, so it should encourage their training as active political subjects from the pedagogical work.